COMMUNITY BASED TOURISM DALAM PENGEMBANGAN PARIWISATA DI DESA NGARGOGONDO KECAMATAN BOROBUDUR KABUPATEN MAGELANG - Tri Asih Wismaningtyas; Ari Mukti; Yuni Kurniasih; Rizza Arge Winata; Fadlurrahman Fadlurrahman; Sri Suwitri; Sri Mulyani; Hendrarto Hendrarto (Jurnal Pemerintahan dan Politik, 2022)
ABSTRACTThe development of Community Based Tourism (CBT) places the community as the main actor in various tourism activities so that the benefits are fully allocated to the local community. Ngargogondo Village has natural potential, human resource potential and strong cultural potential to be developed into a tourist attraction. This research was conducted with a qualitative descriptive method. The research location is in Ngargogondo Village, Borobudur District, Magelang Regency. Data collection techniques through FGD, interviews, observation, and documentation. Informants were selected by purposive sampling technique. The results showed that all aspects of Community Based Tourism (CBT) already existed in the implementation of tourism in Ngargogondo Village. From the aspect of environmental sustainability, the Ngargogondo Village government and parties involved in tourism activities have paid attention to environmental sustainability. This is because the preservation of nature is an attraction for tourists to visit Ngargogondo Village. From the aspect of local culture, this culture still exists in the people of Ngargogondo Village such as Topeng Ireng, Laras Madyo, Hadroh and Rampak Celeng although several other cultures have started to disappear such as Ketoprak, Jathilan and Ndolalak. From the aspect of community participation, the community has initiated the development of Menoreh Teraresing Tourism, Watu Putih Resort, Language Village and Rabbit Park. Then from the aspect of increasing community income, tourism in Ngargogondo Village has a very positive impact, especially for the absorption of labor in tourism objects and the expansion of the small and medium-sized enterprises (SMEs) market. Keywords : CBT; Tourism; Community ABSTRAKPengembangan Community Based Tourism (CBT) menempatkan masyarakat sebagai pelaku utama berbagai kegiatan kepariwisataan sehingga manfaat sepenuhnya diperuntukkan bagi masyarakat lokal. Desa Ngargogondo memiliki potensi alam, potensi sumber daya manusia serta potensi budaya yang kuat untuk dikembangkan menjadi daya tarik wisata. Penelitian ini dilaksanakan dengan metode deskriptif kualitatif. Lokasi penelitian di Desa Ngargogondo, Kecamatan Borobudur, Kabupaten Magelang. Teknik pengumpulan data melalui FGD, wawancara, observasi, dan dokumentasi. Informan dipilih dengan teknik purposive sampling. Hasil penelitian menunjukkan bahwa semua aspek Community Based Tourism (CBT) sudah ada dalam penyelenggaraan wisata di Desa Ngargogondo. Dari aspek keberlanjutan lingkungan, pemerintah Desa Ngargogondo dan pihak yang terlibat dalam kegiatan pariwisata telah memperhatikan kelestarian lingkungan. Hal ini dikarenakan kelestarian alam merupakan daya tarik wisatawan untuk berkunjung ke Desa Ngargogondo. Dari aspek budaya lokal, budaya tersebut masih eksis di masyarakat Desa Ngargogondo seperti Topeng Ireng, Laras Madyo, Hadroh dan Rampak Celeng walau beberapa kebudayaan lain sudah mulai hilang seperti Ketoprak, Jathilan dan Ndolalak. Dari aspek partisipasi masyarakat, masyarakat mempunyai inisiasi dalam pengembangan Wisata Terasering Menoreh, Watu Putih Resort, Desa Bahasa dan Taman Kelinci. Kemudian dari aspek peningkatan pendapatan masyarakat, wisata yang ada  di Desa Ngargogondo memberikan dampak sangat positif khususnya untuk penyeraparan tenaga kerja di objek wisata serta perluasan pasar UMKM. Kata Kunci : CBT; Pariwisata; Masyarakat